On the downward rigidity of wages: Evidence from an experimental labour market with monetary neutrality - Susanna Grundmann; Marcus Giamattei; Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
We run a gift-exchange experiment under conditions of monetary neutrality: aggregate changes in nominal wages leave aggregate real wages unchanged. To achieve this, an employee's real wage is determined by the nominal wage divided by the price level (the average wages paid to others). Recent evidence (Grundmann, Giamattei and Lambsdorff 2019) shows that under these conditions, employees value the employers' intentions in setting nominal wages such that aggregate effort increases in response to increased aggregate nominal wages. We investigate whether this violation of the classical dichotomy leads to downward nominal wage rigidity and whether the violation can be exploited by policy makers. To do this, we implement an exogenous monetary policy shock after the first half of the experiment. Treatments UP and DOWN vary the direction of the shock. We hypothesize, first, that nominal wages exhibit downward rigidity because employers fear that a downward adjustment of the nominal wage would signal bad intentions, and second, that wages are upwardly flexible. We find that employers adjust wages flexibly upward and even excessively downward, while employees do not vary effort in response to the negative shock and reduce effort in response to the positive shock. We discuss possible reasons for these unexpected results as well as implications for our experimental design.
Keywords: C92; E31; E71; 330; gift-exchange game; nominal wage rigidity; monetary neutrality; laboratory experiment; Phillips-curve